Age, skin color, self-rated health, and depression associated with co-occurrence of obesogenic behaviors in university students: a cross-sectional study - Meireles, Adriana Lúcia; Barbosa, Bruna Carolina Rafael; Parajára, Magda do Carmo; Paula, Waléria de; Machado, Elaine Leandro (São Paulo Medical Journal, 2023)
BACKGROUND: The university context plays an important role in the health-disease process since students are potentially vulnerable to obesogenic behaviors that can influence long-term health. OBJECTIVE: To estimate the prevalence of and factors associated with the co-occurrence of obesogenic behaviors among university students. DESIGN AND SETTING: This was a cross-sectional study at a Brazilian public university. METHODS: This study was conducted with all university students in the first and second semesters of 2019 at Universidade Federal de Ouro Preto, Minas Gerais, Brazil. Data were collected between April and September 2019, using a self-administered questionnaire. The outcome was the co-occurrence of obesogenic behaviors, measured as the sum of three risk behaviors: inadequate eating practices, leisure-time physical inactivity, and sedentary behavior. A Venn diagram was used to evaluate the simultaneous occurrence of risk behaviors. Pearson’s chi-square test and multivariate logistic regression were used for statistical analyses. RESULTS: A total of 351 students participated in the study. Inadequate eating practices constituted the most prevalent isolated risk behavior (80.6%), which was also the most prevalent when combined with sedentary behavior (23.6%). University students aged 20 years or younger, with non-white skin color, poor self-rated health, and symptoms of depression had increased chances of simultaneous occurrence of obesogenic behaviors. CONCLUSION: These findings highlight the importance of developing and implementing actions to reduce combined obesogenic behaviors in the university environment. Institutions should focus on creating an environment that promotes health-protective behaviors such as physical activity and healthy eating.